KEARIFAN LOKAL KEMPONAN PADA MASYARAKAT MELAYU DESA SUNGAI KUNYIT LAUT KABUPATEN MEMPAWAH DALAM PANDANGAN AQIDAH DAN AKHLAK ISLAM - Siska Miranda; Rianawati Rianawati; Rizki Susanto (IAIN Pontianak, 2021)
Abstract: The purpose of this study was to examine the local wisdom of kemponan which is still carried out by the Malay community. Kemponan is an expression related to the activity of offering food and drink to other people who have a causal bond when they refuse the offer. This study uses qualitative research to gather information from the community, religious, customary, and community leaders who still apply